What early childhood leadership for what kind of world?. (March 2019) - Aubrey, Carol Anita
This article uses autoethnography as the method of inquiry to explore definitions and contexts of early childhood education leadership. This affords a new space between the subjective and objective, the autobiographical and the cultural, to write in a way that lies between literature and the social sciences. Against a backcloth of scientific and cultural change, five turning-point moments are identified that link personal social circumstances to continuity and change in conceptions of leadership and management, particularly in the early childhood education sector. Modernist hierarchical and more recent subjective or postmodernist models are considered along the way. It is concluded that there is a role for theory in both guiding and interrogating practice. If leaders' conceptions are to be better informed by knowledge of contrasting and competing theories, then through a process of praxis, critical awareness may increase. This depends, however, on access to the training and development that early childhood education professionals do not currently enjoy.